Current Challenges for HER2 Testing in Diagnostic Pathology: State of the Art and Controversial Issues - Sapino, Anna; Goia, Margherita; Recupero, Daniele; Marchio, Caterina (Frontiers in Oncology, 2013)
HER2 overexpression and anti-HER2 agents represent probably the best story of success of individualized therapy in breast cancer. Due to the important therapeutic implications, the issue under the spotlight has been, since ever, the correct identification of true HER2 positivity on tissue specimens. Eligibility to anti-HER2 agents is strictly dependent on the demonstration of HER2 overexpression (by immunohistochemistry) or of HER2 gene amplification by in situ techniques (Fluorescence In Situ Hybridization, FISH), however there are controversial issues involving cases with “equivocal” HER2 status based on conventional techniques (about 20% of specimens). In terms of HER2 expression a major debate is the presence of full-length and truncated forms of the protein and controversial clinical data have been reported on the therapeutic implications of these HER2 fragments. In terms of HER2 gene assessment, the occurrence of amplification of the chromosome 17 centromeric region (CEP17) has been proven responsible for misleading HER2 FISH results, precluding anti-HER2 based therapy to some patients. Finally HER2 activating mutations have been recently described as a biological mechanisms alternative to HER2 gene amplification. In this review we will focus on the controversies that pathologists and oncologists routinely face in the attempt to design the most tailored treatment for breast cancer patients. We will focus on the HER2 gene and on the protein, both at technical and interpretational levels.